Key Tecbnology Application of OTT TV Service Traffic Marketing - Xin Shen; Ying Huang; Feng Wang (Dianxin kexue)
The traffic marketing of OTT TV service was mainly introduced.With the combination of mobile terminals and strong correlation across the screen content technology,O2O service and other business models,the value chain of OTT TV will be extended to the mobile internet and content related services,user-oriented marketing will be a great help to accelerate the develop of OTT TV service.Technologies such as producing using existing content,multi-screen protocol and content associated were described in detai1.Meanwhile,technology solutions such as content organizations,business services and marketing organization with the sharing of users were discussed.